The ultimate retirement guide for 50+ : winning strategies to make your money last a lifetime - Orman, Suze (Hay House, Inc., 2020)
"When you think about planning for retirement-whether it's years in the future or just around the corner-you're bound to have questions. Can I ever afford to stop working? Will Social Security be there for me when I need it? Is the market a safe place for my money? How can I make my money last? Have I waited too long to start saving? Suze Orman, America's most recognized expert on personal finance, answers all the questions that keep you up at night-starting with the biggest one: it is never too late to start planning for a next act that's fulfilling and secure. With her signature blend of compassion, insight, and expertise, Suze guides you toward a plan that will put you in control of your financial future and help you to create the retirement you deserve"--